Preparation method of cationic nanocellulose-based lithium metal battery composite diaphragm
Through the interaction between cationic polyacrylamide and nanocellulose and polypyrrole modification, the pore structure of the nanocellulose-based composite membrane is optimized, the thermal stability and ion transport problems of traditional membranes are solved, and the electrochemical performance of high-performance lithium metal batteries is improved.
Patent Information
- Application Number
- CN202510755669.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-07
- Publication Date
- 2025-09-12
AI Technical Summary
Traditional polyolefin separators have poor thermal stability and wettability, and cannot effectively inhibit the growth of lithium dendrites, resulting in insufficient safety and electrochemical performance of lithium metal batteries. Pure nanocellulose separators have difficulty in ion transport and low ionic conductivity.
Cationic polyacrylamide is used to interact with nanocellulose to optimize the pore structure. The cationic polyacrylamide is evenly coated on the surface of cellulose nanofibers through phase inversion technology, and polypyrrole modification is introduced to enhance the connection strength and ion transmission performance.
The prepared cationic nanocellulose-based composite membrane exhibits good electrolyte absorption capacity and high ionic conductivity, which improves the electrochemical performance of lithium metal batteries and has broad application prospects.
Smart Images

Figure CN120637776A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium metal battery separator preparation, and in particular to a method for preparing a cationic nanocellulose-based lithium metal battery composite separator. Background Art
[0002] As one of the key components of lithium metal batteries, the separator must not only have good mechanical strength and thermal stability, but also provide efficient ion transport channels to ensure battery safety and electrochemical performance. However, traditional polyolefin separators have poor thermal stability and wettability, and are unable to effectively inhibit the growth of lithium dendrites, which can easily cause short circuits and thermal runaway in lithium metal batteries. This makes it difficult to meet the separator requirements of high-performance and high-safety lithium metal batteries. Therefore, the development of new separator materials with excellent thermal stability, high electrolyte wettability, and high ionic conductivity is one of the key factors for the further development of lithium metal batteries.
[0003] Nanocellulose, a naturally renewable, environmentally friendly, and low-cost material, is a popular candidate for lithium metal battery separators. Its abundant hydroxyl groups enhance electrolyte wettability, while its high thermal stability effectively suppresses the risk of thermal runaway, contributing to improved battery safety. However, the dense packing of cellulose nanofibers in pure nanocellulose separators hinders ion transport, resulting in low ionic conductivity and limiting their practical application. Summary of the Invention
[0004] The present invention aims to address the shortcomings of the prior art by providing a method for preparing a cationic nanocellulose-based composite separator for lithium metal batteries. By leveraging the interaction between cationic polyacrylamide and nanocellulose, the pore structure of the nanocellulose-based separator is optimized, thereby improving ion transport performance and ultimately producing a high-performance separator suitable for lithium metal batteries.
[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows.
[0006] The method for preparing a cationic nanocellulose-based lithium metal battery composite diaphragm described in the present invention includes the following steps.
[0007] S1. Dissolve a certain amount of cationic polyacrylamide (molecular weight 10-15 million) in water, place in a water bath, and stir at 80°C for 3 h to form a uniform, transparent, viscous solution.
[0008] S2. After the solution is cooled to room temperature, a certain amount of nanocellulose aqueous dispersion is added and stirred evenly to prepare a nanocellulose / cationic polyacrylamide mixed solution for standby use; wherein the concentration of the diluted nanocellulose aqueous dispersion is 0.1 wt%, and the mass ratio of cationic polyacrylamide to nanocellulose in the mixed solution is 0.2~2.
[0009] S3. Take an appropriate amount of the mixed solution and perform vacuum filtration to prepare a wet film.
[0010] S4. The wet membrane was then immersed in ethanol overnight, during which the ethanol solution was changed several times to ensure sufficient solvent exchange.
[0011] S5. Drying the treated wet film on a hot plate at 60° C. to obtain a cationic nanocellulose-based composite film.
[0012] Furthermore, the nanocellulose is a mixture of one or more cellulose nanofibers prepared from plant cellulose or bacterial cellulose.
[0013] Furthermore, pyrrole was added to the mixed solution of S2, and after uniform mixing, ammonium persulfate solution (10%, wt / v) was added, and the reaction time was ≤12h at room temperature to synthesize polypyrrole and obtain a uniform black mixed solution; wherein the mass ratio of pyrrole to nanocellulose was ≤0.6, and the mass ratio of ammonium persulfate to nanocellulose was ≤1.
[0014] The present invention utilizes the interaction between cationic polyacrylamide and nanocellulose, and uses phase inversion technology to uniformly coat the cationic polyacrylamide on the surface of cellulose nanofibers. This process significantly enhances the connection strength between nanocellulose fibers, thereby significantly improving the performance of the diaphragm. On this basis, we introduced polypyrrole to modify the composite diaphragm, further improving the overall performance of the diaphragm. The preparation process of this type of nanocellulose-based composite diaphragm is simple and environmentally friendly, providing a new design concept for optimizing the performance of nanocellulose-based diaphragms. It also provides a new technical direction for the development of high-energy-density lithium metal batteries.
[0015] The present invention has the following beneficial effects: the cationic nanocellulose-based composite membrane prepared by the present invention uses nanocellulose as a matrix and utilizes the interaction between cationic polyacrylamide and nanocellulose to modify and improve the performance of the nanocellulose-based composite membrane. The process for preparing the cationic nanocellulose-based composite membrane is simple, energy-efficient, and environmentally friendly. The resulting cationic nanocellulose-based composite membrane exhibits excellent electrochemical performance when used as a separator in lithium metal batteries, and has broad application prospects in the field of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1This is a scanning electron microscope image of the cationic nanocellulose-based composite membrane obtained in Example 1 of the present invention.
[0017] Figure 2 This is a scanning electron microscope image of the cationic nanocellulose-based composite membrane obtained in Example 2 of the present invention.
[0018] Figure 3 This is a scanning electron microscope image of the cationic nanocellulose-based composite membrane obtained in Example 3 of the present invention.
[0019] Figure 4 This is a scanning electron microscope image of the cationic nanocellulose-based composite membrane obtained in Example 4 of the present invention.
[0020] Figure 5 3 is a scanning electron microscope image of the nanocellulose membrane obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0021] The present invention will be further described below with reference to specific examples. It should be understood that the examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Example 1
[0022] A method for preparing a cationic nanocellulose-based lithium metal battery composite diaphragm comprises the following steps.
[0023] S1. Dissolve 0.06 g of cationic polyacrylamide (molecular weight 15 million) in 105 mL of water, place in a water bath, and stir at 80°C for 3 h to form a homogeneous, transparent, viscous solution.
[0024] S2. After the solution is cooled to room temperature, 15 g of an aqueous dispersion of nanocellulose (0.8 wt % content) is added and stirred evenly to prepare a nanocellulose / cationic polyacrylamide mixed solution for later use.
[0025] S3. Take an appropriate amount of the mixed solution and perform vacuum filtration to prepare a wet film.
[0026] S4. The wet membrane was then immersed in ethanol overnight, during which the ethanol solution was changed several times to ensure sufficient solvent exchange.
[0027] S5. Drying the treated wet film on a hot plate at 60° C. to obtain a cationic nanocellulose-based composite film. Example 2
[0028] A method for preparing a cationic nanocellulose-based lithium metal battery composite diaphragm comprises the following steps.
[0029] S1. Dissolve 0.12 g of cationic polyacrylamide (molecular weight 15 million) in 105 mL of water, place in a water bath, and stir at 80°C for 3 h to form a homogeneous, transparent, viscous solution.
[0030] S2. After the solution is cooled to room temperature, 15 g of an aqueous dispersion of nanocellulose (0.8 wt % content) is added and stirred evenly to prepare a nanocellulose / cationic polyacrylamide mixed solution for later use.
[0031] S3. Take an appropriate amount of the mixed solution and perform vacuum filtration to prepare a wet film.
[0032] S4. The wet membrane was then immersed in ethanol overnight, during which the ethanol solution was changed several times to ensure sufficient solvent exchange.
[0033] S5. Drying the treated wet film on a hot plate at 60° C. to obtain a cationic nanocellulose-based composite film. Example 3
[0034] A method for preparing a cationic nanocellulose-based lithium metal battery composite diaphragm comprises the following steps.
[0035] S1. Dissolve 0.24 g of cationic polyacrylamide (molecular weight 15 million) in 105 mL of water, place in a water bath, and stir at 80°C for 3 h to form a homogeneous, transparent, viscous solution.
[0036] S2. After the solution is cooled to room temperature, 15 g of an aqueous dispersion of nanocellulose (0.8 wt % content) is added and stirred evenly to prepare a nanocellulose / cationic polyacrylamide mixed solution for later use.
[0037] S3. Take an appropriate amount of the mixed solution and perform vacuum filtration to prepare a wet film.
[0038] S4. The wet membrane was then immersed in ethanol overnight, during which the ethanol solution was changed several times to ensure sufficient solvent exchange.
[0039] S5. Drying the treated wet film on a hot plate at 60° C. to obtain a cationic nanocellulose-based composite film. Example 4
[0040] A method for preparing a cationic nanocellulose-based lithium metal battery composite diaphragm comprises the following steps.
[0041] S1. Dissolve 0.12 g of cationic polyacrylamide (molecular weight 15 million) in 105 mL of water, place in a water bath, and stir at 80°C for 3 h to form a homogeneous, transparent, viscous solution.
[0042] S2. After the solution is cooled to room temperature, 15 g of an aqueous dispersion of nanocellulose (0.8 wt % content) is added and stirred evenly to prepare a nanocellulose / cationic polyacrylamide mixed solution for later use.
[0043] S3. Add 60 μL of pyrrole to the above mixed solution, mix evenly, then add 1 mL of ammonium persulfate solution (10%, wt / v), and react at room temperature for 12 h to synthesize polypyrrole to obtain a uniform black mixed solution.
[0044] S4. Take an appropriate amount of the mixed solution and perform vacuum filtration to prepare a wet film.
[0045] S5. The wet membrane was then immersed in ethanol overnight, during which the ethanol solution was changed several times to ensure sufficient solvent exchange.
[0046] S6. Drying the treated wet film on a hot plate at 60° C. to obtain a cationic nanocellulose-based composite membrane.
[0047] The liquid absorption test results of the cationic nanocellulose-based composite membrane are listed in Table 1.
[0048] The ionic conductivity test results of the cationic nanocellulose-based composite membrane are listed in Table 2.
[0049] A lithium metal battery was assembled using a cationic nanocellulose-based composite membrane as the separator and lithium metal as the negative and positive electrode materials, and its electrochemical performance was tested. The positive electrode sheet was prepared by dissolving PVDF in N-methylpyrrolidone (NMP) to obtain a homogeneous, transparent solution. Subsequently, battery-grade lithium iron phosphate (LiFePO4), Super P, and PVDF were mixed in a mass ratio of 8:1:1. The mixed solution was then ball-milled to form a slurry, coated on aluminum foil, and dried to form the positive electrode sheet. The electrolyte used was 1 M lithium hexafluorophosphate (LiPF6) dissolved in a 1:1:1, by volume, mixture of ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC). Galvanostatic charge and discharge tests were conducted on a Blue Electric battery test system.
[0050] The specific capacity test results of the lithium metal battery assembled with the cationic nanocellulose-based composite membrane under 1C current conditions are listed in Table 3.
[0051] The embodiment is compared and explained below with reference to two comparative examples, as follows.
[0052] Comparative Example 1. Polyolefin commercial separator (model: Celgard 2500).
[0053] Comparative Example 2. The processing steps of the nanocellulose membrane are as follows.
[0054] S1. Prepare 0.1 wt% nanocellulose solution.
[0055] S2. Take an appropriate amount of the above solution and perform vacuum filtration to prepare a wet film.
[0056] S3. The wet membrane was then immersed in ethanol overnight, during which the ethanol solution was changed several times to ensure sufficient solvent exchange.
[0057] S4. Drying the treated wet film on a hot plate at 60° C. to obtain a nanocellulose film.
[0058] The battery assembly process and performance test were the same as in Examples 1-3. The test results are listed in Table 1.
[0059] Table 1
[0060] Table 2
[0061] Table 3
[0062] Cationic polyacrylamide modified nanocellulose prepared a loose, porous cationic nanocellulose-based composite membrane. For example, the morphology of the cationic nanocellulose-based composite membrane obtained in Examples 1-4 (see Figure 1 , 2, 3, 4) and the nanocellulose membrane of comparative example 2 (see Figure 5 ), it was found that the cellulose fibers in the cationic nanocellulose-based composite membranes of Examples 1-4 were more loosely packed and porous than those in the nanocellulose membrane of Comparative Example 2. This indicates that cationic polyacrylamide-modified nanocellulose is conducive to the formation of a looser and more porous cationic nanocellulose-based composite membrane.
[0063] By comparison, it can be seen that the cationic nanocellulose-based composite membrane prepared using the present invention exhibits good electrolyte absorption capacity. For example, the liquid absorption rates of the composite membranes modified with cationic polyacrylamide obtained in Examples 1-4 were as high as 337.1%, 494.4%, 440.6% and 516.7%, respectively (see Table 1). The liquid absorption rate of the nanocellulose membrane of Comparative Example 2, which was not modified with cationic polyacrylamide, was only 240.8%. The liquid absorption rate of the commercial polyolefin separator of Comparative Example 1 was only 131.3%.
[0064] The cationic nanocellulose-based composite membranes prepared by the present invention exhibit high ionic conductivity. For example, the ionic conductivities of the cationic nanocellulose-based composite membranes obtained in Examples 1-4 were 1.19, 1.51, 1.24, and 1.63 mS / cm, respectively. In contrast, the ionic conductivity of the commercial polyolefin separator in Comparative Example 1 was 0.73 mS / cm, and the ionic conductivity of the nanocellulose membrane in Comparative Example 2 was only 0.79 mS / cm (see Table 2).
[0065] The electrochemical performance of lithium metal batteries assembled using the cationic nanocellulose-based composite membrane prepared by the present invention as a diaphragm has also been significantly improved. For example, when charged and discharged under 1C current conditions, the lithium metal batteries assembled with the cationic nanocellulose-based composite membranes prepared in Examples 1-4 have high initial discharge specific capacities (148.4, 151.8, 150.6, and 154.0 mAh / g), while the initial discharge specific capacities of the lithium metal batteries assembled with the polyolefin commercial diaphragm of Comparative Example 1 and the nanocellulose membrane of Comparative Example 2 are 143.0 and 145.5 mAh / g, as shown in Table 3. This shows that the cationic nanocellulose-based composite membrane prepared by the present invention has electrochemical properties that are significantly better than those of commercial membranes and pure nanocellulose membranes.
[0066] In summary, the cationic nanocellulose-based composite membrane for lithium metal batteries prepared by the present invention has excellent electrochemical properties, a simple preparation process, energy saving, and environmental protection, and therefore has broader application prospects.
[0067] The above shows and describes the preparation process and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and description merely describe the method of the present invention. Various changes and modifications are possible without departing from the spirit and scope of the present invention. Such changes and modifications are intended to fall within the scope of the claimed invention. The scope of protection claimed by the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a cationic nanocellulose-based lithium metal battery composite diaphragm, characterized in that The steps include: S1. Dissolve a certain mass of cationic polyacrylamide with a molecular weight of 10 to 15 million in water, place in a water bath, and stir at 80°C for 3 h to form a uniform, transparent, viscous solution; S2. After the solution is cooled to room temperature, a certain amount of an aqueous dispersion of nanocellulose is added and stirred evenly to prepare a mixed solution of nanocellulose / cationic polyacrylamide for standby use; wherein the concentration of the diluted aqueous dispersion of nanocellulose is 0.1 wt%, and the mass ratio of cationic polyacrylamide to nanocellulose in the mixed solution is 0.2-2; S3, taking an appropriate amount of the mixed solution and performing vacuum filtration to prepare a wet film; S4, then immerse the wet membrane in ethanol overnight, changing the ethanol solution several times to ensure sufficient solvent exchange; S5. Drying the treated wet film on a hot plate at 60° C. to obtain a cationic nanocellulose-based composite film.
2. The method for preparing a cationic nanocellulose-based lithium metal battery composite diaphragm according to claim 1, characterized in that The nanocellulose is a mixture of one or more cellulose nanofibers prepared from plant cellulose or bacterial cellulose.
3. The method for preparing a cationic nanocellulose-based lithium metal battery composite diaphragm according to claim 1, characterized in that Pyrrole was added to the mixed solution of S2, and after uniform mixing, a 10% (wt / v) ammonium persulfate solution was added. The reaction time was ≤12h at room temperature to synthesize polypyrrole and obtain a uniform black mixed solution; wherein the mass ratio of pyrrole to nanocellulose was ≤0.6, and the mass ratio of ammonium persulfate to nanocellulose was ≤1.